The Origin and Narrative Function of the Conquest of the Land (2 Kgs 17:5a) in the Account of the Fall of Samaria (2 Kgs 17:3–6) - Krzysztof Kinowski (The Biblical Annals, 2025)
The conquest of the land in 2 Kgs 17:5 is the key element in the account of the fall of Samaria (2 Kgs 17:3–6). The source analysis of this verse leads to the conclusion that its shorter version, witnessed by the Old Latin Palimpsestus Vindobonensis (La115) where the conquest of the land is not mentioned, may be the oldest recoverable form of this text, allowing for the reconstruction of the true Old Greek text and its Hebrew Vorlage, in this regard alternative to the longer version attested to by the Masoretic text. The survey on the possible reasons underlying the postulated textual expansion in 2 Kgs 17:5MT indicates that the mention of the attack on the entire country adds drama to the events narrated, emphasises the totality of the Assyrian invasion, and makes the capture of Samaria more significant. In contrast, the lectio brevior of the OL appears to be less dramatic and somehow ‘flat’ from the narrative point of view. In this way the narrative of the lectio longior takes on an increasingly anti-Samarian tone disclosing possible pragmatic motives underlying postulated textual expansions. Historical contextualisation of the events narrated in 2 Kgs 17:5MT completes the picture, which seems to be much more complex than the straightforward biblical narrative would suggest. The final literary context in which these events are narrated indicates that the biblical editor is mostly interested in theodicy to depict the total defeat of Samaria and the definitive end of the Kingdom of Israel in theological terms. In this regard, the remark about the conquest of the land in the MT, in later Greek versions, and the Targum, intensifies the anti-Samarian rhetoric of the biblical text in comparison with those textual versions which do not mention it (OL and several Greek testimonies).